Neorealism and Russian balancing in Europe - Maitra, Sumantra (2021)
What explains Russian balancing behaviour and use of military force in Europe? Over the last decade and a half, shifting geopolitical setting in Europe renewed the question about Russian military capabilities and strategic intentions. Exacerbating the shift has been the evolving balancing behaviour of Russia regarding NATO and use of military force in Ukraine and Georgia. Recent literature, and conventional wisdom attribute Russian military posture and use of force in Europe primarily to domestic politics, but also to Christian conservatism, civilisational exceptionalism, imperial expansionism, and domestic factors like diversionary war and regime stability. My thesis attempts to test Russian post-soviet foreign policy, balancing behaviour, and use of military force in Europe, in light of Stephen Walt’s Balance of Threat theory. Moscow indulges in the military use of force and balancing behaviour, only when it perceives its interests to be threatened, but seeks to preserve, uphold, or return to the status-quo the moment the threats, subside or are neutralised by balancing actions, acting more as a security maximiser, than a power maximiser. The thesis employs a qualitative research design and case study method, relying on secondary literature, military sources, and observed and recorded news. The evidence relies on Russian strategic actions, and not Russian rhetoric. The evidence explored suggests that, first, Russia balances against perceived threats, and Russian use of force is directly proportional to any strategic and material loss. Alternatively, Russia behaves like a status quo power, when the perceived threat subsides. Second, Russian military aggression is focused on geopolitical balance and has narrow strategic aims, and Russia either lacks the will and/or capability, or both, to be an expansionist or occupying power. Third, Russia is inherently a reactive power with limited regional aims, which are not commensurate with an aspiration of a continental hegemony. The findings have future policy relevance for European/British security, as the U.S. grows increasingly isolationist, and NATO and EU rift widens.